Optimization of Quillbot Utilization in The Preparation of Scientific Papers by Teachers at SMA Negeri 2 Parepare, South Sulawesi - Rahmi, Nur; Ekasasmita, Wahyuni; Miftahulkhairah, Miftahulkhairah; Fajri S, Ahmad; Lawi, Armin; Sir, Muhammad Mochsen; Latunra, Andi Ilham; Anggitamaya, Anggitamaya; Amal, Muhammad Ikhlasul (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Writing scientific work is an important indicator of the development of knowledge and critical thinking. But still, many teachers have difficulty writing scientific papers, including avoiding plagiarism. The dedication to the society conducted by the Bacharuddin Institute of Technology team Jusuf Habibie aims to improve the skills of teachers at 2 Parepare State High School in reducing the risk of plagiarism in the writing of scientific works through optimization of the use of QuillBot and implementation of paraphrase techniques in writing. The method used is ABCD (asset-based community development). The activities include identification of needs, planning based on problem analysis, preparation of training material books, training on paraphrase techniques and QuillBot, and evaluation of writing quality as well as the effectiveness of training by participants. The training was held on June 6, 2024, followed by 26 participants. The average pretest for the Similarity Index (SI) writing percentage of participants was 54.62%, while the average posttest value for the participant's SI writing percent was 37.85%, with an average SI decrease of 16.77%, showing this training has proven to be effective in reducing the rate of plagiarism among participants. A total of 21 of the 26 participants, or 80.8% of the participants, succeeded in reducing the level of plagiarism in their writings. Thus, this dedication program succeeds in helping teachers improve their skills in writing scientific papers to avoid plagiarism.